Experiential Learning within the Process of Opportunity Identification and Exploitation - Corbett, Andrew C. (Entrepreneurship Theory and Practice, 2005)
The article uses experiential learning theory to magnify the importance of learning within the process of entrepreneurship. Previous research details the contributions of prior knowledge, creativity, and cognitive mechanisms to the process of opportunity identification and exploitation; however, the literature is devoid of work that directly addresses learning. The extant research assumes learning is occurring but does not directly address the importance of learning to the process. To fully understand the nature of the entrepreneurial process, researchers must take into account how individuals learn and how different modes of learning influence opportunity identification and exploitation. This article makes connections between knowledge, cognition, and creativity to develop the concept of learning asymmetries and illustrates how a greater appreciation for the differences in individual learning will fortify entrepreneurship research.